Evaluasi Kinerja Pengelolaan Dana Transfer Pusat Ke Daerah Dan Dampaknya Terhadap Pembangunan Daerah Provinsi Kalimantan Tengah - Vennus Octolongerens; Alexandra Hukom (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to evaluate the performance of management of transfer funds from the central to regional government and its impact on development in Central Kalimantan Province. The method used is descriptive analysis with a qualitative and quantitative approach to measure effectiveness, efficiency and accountability in managing these funds. The research results show that the management of transfer funds in Central Kalimantan has been implemented quite well, but there are still several obstacles in the aspects of budget absorption and supervision. The impact of transfer fund management on regional development can be seen from improvements in infrastructure, education and health. However, to achieve more optimal results, it is necessary to increase the capacity of local human resources and a more effective monitoring system.